Role of Mass Literacy, Adult and Non-formal Education to National Development in Nigeria - Odo, Michael Eze (International Journal of Educational Management, 2025)
The National Policy on Education (2014) captures Mass Literacy, Adult and Non Formal Education as programmes equivalent to Basic Education for adults, youth and children of formal school age outside the conventional education system. The essence was to provide basic education to disadvantaged group of people who have dropped out of schools or never had the opportunity of schooling but wish to acquire basic literacy of reading, writing and arithmetic. The paper critically looked at the concepts and practices of mass literacy, adult and non-formal education in Nigeria. it further examined the historical perspective and status of mass literacy in the country. It also highlighted on its key contributions to community and national development such as provision of needed manpower to enhance national productivity and acquisition of competencies needed for self-reliance as productive Nigeria citizens. It drew a conclusion that mass literacy campaign in Nigeria is gaining acceptance going by the literacy rate of 62.02% from the estimated population of 200 million Nigerians with 71.26% male literacy over and above 52.66% female literacy rate.